Developmentof the University of the Philippines Mindanao integrated information management system web-based faculty merit for promotion module - Plaza, Ian Jay C. (2010)
Recommendation or recommender systems are develop to help an individual or organization in generating solutions to problems. In the human relations field, recommender systems greatly help in decisions regarding human resource development. This study was conducted to develop a web application that allows the storage and submission of documents by faculty , evaluation of the documents by evaluators, initiation of the promotion process by the Human Rsource Officer and recommendation of the system qualified applicants for promotion. Three modules were created to address these needs, namely, the Faculty module, Evaluator Module and Human Resource Officer Module with the use of PHP, MySQL and JavaScript, specially the jQuery library which handles the animations used by the system. The faculty module was created to enable the faculty to register as applicants to be able to store and submit documents to be used in the application for a promotion call. This module also stores the record af all promotion applications of the faculty. The Evaluator Module enables the evaluator to review and evaluate the applicants' submitted documents which will be the basis af an applicant's accumulated points. The Human Resource Officer Module allows the user to issue calls, initiate and end a promotion process, compose the group of evaluators, add criteria and approve an application based on the systems recommendation. The basis for the recommendation is the comparison of the applicant's accumulated points with the current promotion call's point quota. Applicants with accumulated points equal or greater than the call's quota are recommended. With the use of simple point comparison, the system develop became a recommender system for the grant of a promotion aside from being a repository of faculty documents.
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2010
Keywords: Web application; Recommender systems; Recommendation systems; Promotion process